PROBLEMATIKA SERTA UPAYA MENINGKATKAN KETERAMPILAN MENULIS DI KELAS TINGGI SISWA MI/SD - Defi Antika; Khairunnisa Khairunnisa; Linda Damayanti; Salsabila Saragih; Muliana Fitri Lingga (Pusat Riset dan Inovasi Nasional, 2023)
Language has four skills, namely listening, speaking, reading and writing skills. The lack of advanced writing skills in high grades in MI/SD is due to the lack of use of innovative learning methods which are still not optimal. So in this case the teacher must change the learning situation so that it is more active by choosing the right method. This study aims to determine; (1) What are the problems that affect low advanced writing skills in high grades, (2) What are the methods to improve aspects of advanced writing skills in high grades. The research uses the library research method, namely by examining scientific sources such as related books and journals. The research results are; (1) Knowing what are the problems that affect low advanced writing skills in high grades (2) Knowing the methods used by teachers to improve aspects of advanced writing skills in high grades.